ANALISIS TERHADAP WARIS ANAK ANGKAT BERDASARKAN HUKUM ISLAM (STUDI PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 677/K/AG/2009) - Dewi, Santy; Hanifah, Mardalena; Ghafur, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
In Indonesia, the rule of Allah on this inheritance into positive law used in the Religious Court in deciding the case of division or dispute relating to inheritance. The authors took a sample case of the Supreme Court Number 677/K/AG/2009, which is the case in the cassation decision of the High Court of Bandung Religion Number 63/Pdt.G/2009/PTA.Bdg which is also the appeal decision of testamentary inheritance dispute case in the Religious Bandung Number 747/Pdt.G/2008/PA/Bdg . The purpose from written this scripsion are; The First, the basic legal considerations of the Supreme Court in deciding the case of inheritance disputes testament Number 677/K/AG/2009. The Second, the decision of the judges of the Supreme Court in determining the division of inheritance based on Islamic law meets the principle of legal certainty. The conclusion are, The first, consideration of law in the Supreme Court Decision Number 677/K/AG/2009 has been correct in applying the law of inheritance relating to wills as the considerations, as an adopted child only receives one-third of the estate, it is appropriate Article 209 KHI. The second, the judges had been thorough in examining and deciding the case in the Supreme Court Decision Number 677/K/AG/2009, so that the judges had been correct in applying the legal basis in the consideration that resulted in lack of legal certainty in the decision decided by the judge concerning the rights rights which should be accepted by the legitimate heir. Writter suggest, The first, in considering a case the judge must consider the principle of legal certainty , fairness and expediency of any litigants. The second, the rule of law is a form of protection against individuals who the arbitrary with other individuals. Therefore, judges must pay attention to the rule of law as a form of protection against arbitrary actions committed by individuals against other individuals and pay attention to the rights that should be accepted as a form of legal certainty.Key words : Inheritance Testament – Islamic Law – Supreme Court Decision Number677/K/AG/2009